Manajemen Tenaga Pendidik Dan Kependidikan - Khoirul Bariyyah; Fitri Rahayu; Maulana Muhammad Taufiqi (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The management of teaching and educational staff is an activity that must be carried out starting from the teaching and education staff entering the educational organization until it finally stops through the process of HR planning, procurement, placement, awarding of compensation, awards, education and training development and termination. The management of educational staff (teachers and staff) absolutely must be implemented by school principals so that they can utilize educational staff effectively and efficiently to achieve optimal results. In accordance with this, a school principal must be able to find, position, evaluate, direct, motivate, and develop the talents of each teacher and staff and be able to align individual and organizational goals. Management is the science and art of managing the process of using human resources effectively, which is supported by other sources within the organization to achieve certain goals. In the world of education, human resources that we know are educators and educational staff, or what we often call teachers. For the success of an educational institution there are several things that need to be considered in the management of teaching and educational staff. The activities carried out in the management of teaching and educational staff begin with employee planning, employee procurement, employee coaching and development, promotions and transfers, employee dismissals and finally employee performance appraisal. Each stage is carried out in a coherent manner to produce qualified teaching and educational staff professional, reliable and efficient. Furthermore, regarding the explanation of the criteria for an educator and Islamic education based on the Qur'an and Hadith. It is hoped that with the running of teaching and educational staff management activities it can support the process of teaching and learning activities in an educational institution in accordance with the goals of the national education system. Teaching staff and education staff realize several main aspects in the competency development program for teaching staff and education staff.